Biomechanical Evaluation of Four Methods for Internal Fixation of Comminuted Subtrochanteric Fractures. Issue 19 (May 2016) - Wang, Jie; Ma, Jian-xiong; Jia, Hao-bo; Chen, Yang; Yang, Yang; Ma, Xin-long
Abstract : Abstract: Subtrochanteric fractures are common and result in significant morbidity and mortality. Various kinds of implants have been used to fix it. The aim of this study was to compare the biomechanical performance of PFN, DHS, DCS, and the PFLP in the treatment of subtrochanteric comminuted fractures. A total of 32 antiseptic human femurs from 16 donors were randomly allocated to 4 groups for fixation with PFN, DHS, DCS, and PFLP. A 2-cm cylindrical bone fragment was removed 1 cm below the lesser trochanter to simulate OTA/AO 32-C3.2 post instrumentation fracture. All specimens in single-leg stance situation were preloaded 5 times at 100 N in the axial direction to eliminate the time effect of relaxation and settling, followed by cyclic testing at a rate of 1 Hz with stepwise increasing load. Keeping the valley load at a constant level of 100 N during the entire cyclic test, the peak load, starting at 200 N, was increased by 100 N at 300-cycle steps until a maximum of 1500 cycles or until failure of the bone-implant construct occurred. Each specimen was kept unloaded under 100 N compression for 30 minutes between the 300-cycle steps. Femoral head displacement after 1500 cycles was 1.09 mm ± 0.13 for PFN, 1.78 mm ± 0.25 for DHS, 2.63 mm ± 0.46 for DCS, and 2.26 mm ± 0.16 for PFLP, with significant difference between any 2 implants ( P  < 0.01). The required load to reach 1-mm femoral head displacement was 563.04 N ± 158.34 for PFN, 485.73 N ± 147.27 for DHS, 258.44 N ± 97.23 for DCS, and 332.68 N ± 100.34 for PFLP. Significant differences were detected between any 2 implants ( P  < 0.001), except between DCS and PFLP and between DHS and PFN. The number of cycles until 1-mm femoral head displacement was 1458 ± 277 for PFN, 908 ± 184 for DHS, 369 ± 116 for DCS, and 603 ± 162 for PFLP. Significant differences were detected between any 2 implants ( P  < 0.01), except between DCS and PFLP. From biomechanical point of view, comminuted subtrochanteric fractures OTA/AO 32-C3.2 revealed in the current test setup highest fixation strength with PFN, followed by DHS, PFLP, and DCS.